LEGAL POLICY OF INFORMATION TECHNOLOGY BASED STOCK SERVICES IN THE CAPITAL MARKET - Nadirah, Ida (Proceeding International Seminar of Islamic Studies, 2023)
In the current digital era, information technology has been widely used for the development of the financial industry which encourages the growth of alternative financing for the business world, especially start-ups or novice business actors as a means of investment for the community. This is in line with the establishment of RI Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE) which aims to realize clean, effective, transparent, accountable, as well as quality and reliable governance. One form of its activity is Crowdfunding Services Through Information Technology-Based Stock Offerings (Equity Crowdfunding), namely stock offering services carried out by issuers to sell shares directly to investors through an open network of electronic systems. This type of research is normative juridical with a statutory approach and legal principles. Using data sourced from secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials which are then analyzed qualitatively. The results of the study show that with the existence of policies regarding the implementation of crowdfunding services through information technology-based stock offerings, the national economy accelerates because in transactions using electronic media that is more practical, makes it easier for people to make transactions, develops trade and the national economy, and realizes financial inclusion targeted by the government